DARI AMANAH KE KEUNGGULAN: TRANSFORMASI NILAI ISLAM DALAM KEPEMIMPINAN BISNIS MODERN - Maulana Rahman, Dimas; Zianda Alfarizzaki, Muhammad (Yayasan An-Nur Meunara Baro, 2025)
This article aims to analyze the transformation of Islamic values in modern business leadership, focusing on how the concept of amanah (trustworthiness) serves as the foundation for organizational excellence. In today’s competitive business environment, ethical and moral crises have emerged as major challenges for sustainable leadership. Using a qualitative descriptive approach based on literature analysis, this study finds that Islamic principles such as amanah (trust), ‘adl (justice), ihsan (professional excellence), and syura (consultation) remain highly relevant to contemporary management practices. Islamic leadership is not solely profit-oriented but also emphasizes social welfare and collective benefit. These values play a crucial role in shaping leader integrity, fostering organizational trust, and establishing a fair and sustainable work culture. The findings indicate that integrating Islamic values into business leadership strengthens the spiritual and ethical dimensions of modern organizational governance. Consequently, an Islamic value-based leadership model offers an alternative paradigm that harmonizes spirituality and professionalism in pursuit of ethical, just, and dignified business excellence.